Nutrition Education and Assistance Based on Behavior Change in Adolescent Girls to Improve Nutritional Status and Hemoglobin Levels - Amalia Rahma; Sholikhah, Desty Muzarofatus; Nur Cahyadi; Endah Mulyani; Zuhroh, Diah Fauziah; Has, Dwi Faqihatus S. (Universitas Airlangga, 2023)
Inappropriate nutritional behavior is a common cause of nutritional issues among adolescents, often leading to conditions like underweight and anemia. This study aimed to assess the impact of nutrition education and behavioral change-based support on the nutritional status and hemoglobin levels of adolescent girls. The study included 75 adolescent girls aged 16-18 years from Singosari Village, Gresik District, chosen through purposive sampling. Over a 30-day period, intensive nutrition education and assistance were provided, utilizing various methods such as lectures, discussions, role play, and practical exercises. The results revealed significant improvements in various aspects. Participants exhibited increased nutrition knowledge, energy and protein intake, body weight, nutritional status, and hemoglobin levels after the intervention (p < 0.05). The rise in knowledge was linked to higher protein intake (p=0.009), while adequate protein intake was associated with weight gain (p=0.025). Weight gain, in turn, correlated significantly with improved nutritional status based on BMI/U (p = 0.041). Hemoglobin levels also significantly increased, shifting from 11.6 + 0.2 mg/dl (low) to 13.4 + 0.1 mg/dl (normal) after the intervention. This improvement in hemoglobin levels was linked to increased energy intake (p = 0.012) and a change in the practice of consuming iron supplementation, shifting from no usage to weekly consumption. In conclusion, nutrition education and behavioral change-based support can effectively enhance energy, protein, and iron intake, leading to improved nutritional status and hemoglobin levels among adolescent girls.